1992
DOI: 10.1128/jb.174.20.6659-6665.1992
|View full text |Cite
|
Sign up to set email alerts
|

Role of the origin of transfer in termination of strand transfer during bacterial conjugation

Abstract: Conjugal transfer of the broad-host-range plasmid R1162 is initiated and terminated at the nic site within the 38-bp origin of transfer (oriT). Termination involves ligation of the transferred single strand by the plasmid-encoded MobA protein. Several different assays were used to identify the oriT DNA required for termination. For plasmids containing two oniTs, with transfer initiated at one and terminated at the other, the inverted repeat within oniT is-important for termination. Deletion of the outer arm re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…A different termination nicking reaction for R1162 was engineered by placing a second oriT "downstream" from the first, in terms of the direction of DNA transfer. The termination/recircularization event at the second oriT was prevented if the inverted repeat within this oriT was removed, consistent with the hypothesis described above (81).…”
Section: Dna Recircularization Complementary Strand Synthesis and Vsupporting
confidence: 72%
“…A different termination nicking reaction for R1162 was engineered by placing a second oriT "downstream" from the first, in terms of the direction of DNA transfer. The termination/recircularization event at the second oriT was prevented if the inverted repeat within this oriT was removed, consistent with the hypothesis described above (81).…”
Section: Dna Recircularization Complementary Strand Synthesis and Vsupporting
confidence: 72%
“…We have suggested that these steps involve the same reaction, carried out by the MobA protein and requiring a similar substrate (Zhang and Meyer, 1995). In each case, MobA cleaves within a single-stranded region, but requires adjacent duplex DNA at the inner arm of the inverted repeat for tight binding (Bhattacharjee et al, 1992;Bhattacharjee and Meyer, 1993). In the case of the single, transferred strand, a duplex structure adjacent to the cleavage site is generated by basepairing between the arms of the inverted repeat (Barlett et al, 1990;Bhattacharjee and Meyer, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids used in this study are listed in Table 3. Conjugal matings were carried out on semi-solid media essentially as described in previous publications (Brasch and Meyer, 1986;Bhattacharjee et al, 1992), with donor MV10 or LE316 cells containing the IncP-1 plasmid R751 as mobilizing vector (Willetts and Crowther, 1981). The recipient strain was DF1019, a C600 derivative resistant to nalidixic acid (Figurski et al, 1976).…”
Section: Strains Plasmids and Bacteriological Proceduresmentioning
confidence: 99%
“…Three R1162 proteins, MobA, MobB, and MobC, form a protein-DNA complex called the relaxosome at oriT (27). From the mobilization experiments with recombinant plasmids containing two tandemly repeated oriT sequences with or without mutations, the 10-bp inverted repeat structure as well as the sequence around the nick site was shown to be required for termination, while the nick site-distal arm of the inverted repeat was not required for initiation (1). From the analyses of mutations introduced into the 10-bp repeat, it has been postulated that during termination of DNA transfer, formation of a hairpin loop structure by the inverted repeat is required for the resealing of the transferred DNA by the R1162 MobA relaxase (32).…”
mentioning
confidence: 99%